Carbon Nanotube/Graphene Nanoplatelet Hybrid Film as a Flexible Multifunctional Sensor - JianRen Huang; XiaoXiang Yang; Shiuh-Chuan Her; Yuan-Ming Liang (Sensors, 2019)
A flexible hybrid film consisting of graphene nanoplatelets (GNPs) and multi-walled carbon nanotubes (MWCNTs) was prepared and employed as a multifunctional sensor to monitor temperature and liquid leakage, based on the piezoresistive effect. The influences of the GNP content on the mechanical, thermal, and sensing properties were investigated. Experimental results showed that both the hardness and Young’s modulus of the hybrid film were decreased with an increasing GNP content, while the thermal conductivity exhibited in an opposite trend. The electrical resistance of the hybrid film decreased was linearly with an increase in temperature. The resistance change increased linearly with an increase of the solvent adsorption. These features demonstrated the potential applications of the hybrid film in the detection of temperature, and liquid leakage. The sensitivity of leakage detection is increasing with the increase of the GNP loading, while temperature sensitivity is in the opposite trend.